A Retrospective Evaluation Of Type Of Impression Technique Used In Complete Denture Fabrication By Dental Students - REDDY, DR. M.SAI TEJA; AHMED, DR. NABEEL; SASHANKA, DR. KEERTHI (The journal of contemporary issues in business and government, 2021)
Purpose: The aim of this study was to retrospectively evaluate the type of impression technique used in complete denture fabrication among dental students. Materials And Method: A total of 510 data entries were taken, duplicate and missing entries were omitted. So a total of 484 entries were evaluated. The data was collected from patient records in Saveetha Dental College, over a period of one year. The evaluation was based on the technique used in primary impression by the dental students for complete denture fabrication. Statistical Analysis:The results of the study were subjected to statistical analysis. Data analysis was done using SPSS software version 23.0. Frequency evaluation and Chi-square test was done to evaluate the most frequently used technique used to fabricate complete denture. Results: It was found that about 47.2% was using mucocompressive technique, 37.5% was using mucostatic impression technique and 15.3% was using selective pressure technique. Conclusion:The present study concluded that most of the dental students have preferred to use mucocompressive technique for denture fabrication.